Expansion Strategy of the Event & Travel Agency Edison into the Czech Market - Žanonyová, Diana (2024)
The main goal of expansion of the Slovak based event & travel agency to the Czech market is the potential of getting new customers, as well as building the brands name. The first part will examine and analyse the potential strengths, weaknesses, opportunities, and threats of the market. Another analysis will be the PESTEL. Later, the research will be focused on the company and its potential. Based on these researches. I will choose the best model of entry to the Czech market. Research question: RQ1: What would be the market entry strategies and factors chosen to achieve the most successful and profitable expansion of the event & travel agency edison into the Czech Market? H2: Choosing the best strategic marketing and promotion of the company, tailored exactly for the Czech customers is necessary for raising brand awareness, generating interest, and acquiring a customer base in the Czech market. H3: Analysing and identifying market segments and niches in the Czech market are the key aspects for the company to have competitive advantage and growth in the Market.